Spindle cell sarcoma of uterus-a rare tale - Maini, Manvi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Uterine sarcoma are a heterologous group of are malignancies and account for one-tenth of uterine malignancies. Presentation of uterine sarcomas are usually very non-specific and varies with the histological sub type. Here we discuss a rare case of spindle cell neoplasm which presented to us with massive abdominal enlargement.she had no pressure symptoms. Decision to perform an exploratory laparotomy was taken given the high suspicion of ovarian tumour. Diagnosis was confirmed after histopathological report. Patient is doing well on follow up.